EVALUATION OF PASSPORT SERVICE QUALITY THROUGH THE M-PASPOR APPLICATION IN SIMPLIFYING SERVICES AT THE CLASS I SPECIAL IMMIGRATION OFFICE, TPI SURABAYA - Hafids Sutatak; Fedianty Augustinah; Ika Devy Pramudiana; Sri Kamariyah (DIA: Jurnal Administrasi Publik, 2025)
The development of information technology has driven the transformation of public services, including in the immigration sector, which is now transitioning to digitalization to improve efficiency. One of the innovations introduced is the M-Paspor application, which allows the public to apply for passports online to minimize classic issues such as long queues and bureaucratic inefficiencies. This study aims to evaluate the quality of passport services through the M-Paspor application at the Immigration Office Class I Special TPI Surabaya and identify challenges and opportunities in simplifying public services. The research employs a qualitative method to explore the perceptions and experiences of the public and immigration officers regarding the use of the M-Paspor application. Data were collected through in-depth interviews with passport applicants and immigration officers, as well as direct observations of service processes at the immigration office. The evaluation focuses on five dimensions of service quality: reliability, assurance, tangibles, empathy, and responsiveness, to provide a comprehensive understanding of the application's effectiveness in simplifying public services. The findings indicate that although the M-Paspor application has reduced some bureaucratic issues, several challenges remain, particularly concerning system reliability and the public's ability to use technology. Some users continue to face technical difficulties, such as frequent server errors, rapidly filled service quotas, and data entry errors that require them to repeat the registration process. The study concludes that while the M-Paspor application holds great potential to improve passport service quality, significant improvements in system stability, user education, and technological infrastructure are needed to achieve optimal results.